CIS in Meouane - Carney, Tanya (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate Information Services (CIS) are decision-making support tools that provide information including scientific weather and climate forecasts, market prices, and adaptive practices directly to users. By providing real-time information to support agricultural decisions it is believed that productivity can be increased and incomes and livelihoods can be improved.